Elisa testing for Brucellosis in Southern Albania: preliminary results for Brucellosis prevelance and incidence rate in a hot zone - Kouvelas, George J.; Alexopoulou, Amalia Ε.; Sarafis, Pavlos (My University, 2008)
Objective To determine the number of Brucellosis cases (new and past cases) in a sample of subjects coming from the Greek Albanian Hospital in Gjirokaster, in Southern Albania. Methods In a 3-month period, June 2006 - September 2006, 1040 patients were examined in the Internal Medicine out-patient Clinic. The eligibility criteria included information based on the medical history, clinical examination and serological ELISA tests (IgM- IgG), collected to form two study groups for our retrospective study. Group A included asymptomatic subjects and Group B symptomatic ones. In both groups we detected the number of new cases (indicating preliminary information for the incidence rate in the area) and the total number of Brucellosis cases( representing preliminary information for the disease prevalence in Southern Albania), and we discussed the aspects of the disease clinical appearance based on our findings. Results In the 3-month period of the study, we diagnosed 6 new symptomatic patients with brucellosis (IgM +) and 32 immuno-positive patients (lgG+).The total brucellosis cases was the 3,65% and the new cases was the 0,93%, both significant statistically in comparison to the officially reported prevalence of Brucellosis in Albania and other countries. Conclusions These preliminary results suggest that Brucella is a present threat in Southern Albania. There is apparently a need for massive control and revision of the existing public health policies in collaboration to governmental organizations of the country.
Keywords: Brucellosis; Undulant fever; Malta fever; Alphaproteobacteria; Vaccine; Zoonoses